Optical Properties of Materials in an Undergraduate Physics Curriculum - Blanco, Julio R. (EPIOPTICS-8, 2006)
The need to introduce physics undergraduates to non-traditional subjects is ever increasing due to the job opportunities in interdisciplinary fields. The traditional upper-level curricula after the standard sequence in introductory calculus-based physics is challenging to many students. Adding more elective requirements is not in vogue with university administrators that must deal with a large influx of students with fewer resources. Experimental physics lends itself well to introduce students to interdisciplinary concepts. At California State University Northridge (CSUN), we have introduced modules in experimental physics to meet this need. All juniors and seniors are required to take two units of experimental physics per semester, a total of eight units. An experimental unit represents three contact hours per week. Each two units consist of two modules, each lasting seven and a half weeks, six hours per week. One of these modules exposes the students to thin film deposition by sputtering, imaging by scanning electron microscopy, and optical characterization using scanning ellipsometry. This early exposure to interdisciplinary applied physics motivates students and identifies difficulties with fundamental concepts.